Technology-Based Care Model: Building a Sustainable Nursing System in Disadvantaged Areas - Rizka Adela Fatsena; Dina Ahmed; Mona Abdallah; Siska Indrayani (Yayasan Adra Karima Hubbi, 2025)
In disadvantaged areas, limited access to healthcare services poses significant challenges to achieving equitable health outcomes. The integration of technology in healthcare systems has been proposed as a solution to bridge gaps in access and quality, particularly in nursing care. This research explores the effectiveness of a technology-based care model in building a sustainable nursing system in underserved regions. The study utilizes a mixed-methods approach, combining quantitative data on health outcomes with qualitative insights from healthcare providers and patients. The findings indicate that technology-based interventions, such as telemedicine, mobile health applications, and remote patient monitoring, led to a 20% improvement in patient outcomes and a 30% reduction in healthcare delivery costs. Additionally, healthcare providers reported increased efficiency and job satisfaction due to the support offered by technology in monitoring patient conditions and facilitating remote consultations. The study concludes that the adoption of technology-driven care models can significantly enhance nursing systems in disadvantaged areas by improving accessibility, efficiency, and sustainability of care. However, challenges related to infrastructure, training, and data security must be addressed to ensure the success of such models. Future research should focus on scaling these models to other resource-limited settings and assessing their long-term impact.